Exploring Publishing Patterns at a Large Research University: Implications for Library Practice - Amos, Kathleen; Mower, Allyson; James, Mary Ann; Weber, Alice; Yaffe, Joanne; Youngkin, Mary (Evidence Based Library and Information Practice, 2012)
Objective – The research project sought to explore the value of data on publication patterns for decision-making regarding scholarly communications and collection development programs at a research-intensive post-secondary institution, the University of Utah in the United States. Methods – Publication data for prolific University of Utah authors were gathered from Scopus for the year 2009. The availability to University of Utah faculty, staff, and students of the journals in which University of Utah authors published was determined using the University of Utah Libraries’ catalogue; usage was estimated based on publisher-provided download statistics and requests through interlibrary loan; and costs were calculated from invoices, a periodicals directory, and publisher websites and communications. Indicators of value included the cost-per-use of journals to which the University of Utah Libraries subscribed, a comparison of interlibrary loan costs to subscription costs for journals to which the University of Utah Libraries did not subscribe, the relationship between publishing venue and usage, and the relationship between publishing venue and cost-per-use. Results – There were 22 University of Utah authors who published 10 or more articles in 2009. Collectively, these authors produced 275 articles in 162 journals. The University of Utah provided access through library subscriptions to 83% of the journals for which access, usage, and cost data were available, with widely varying usage and at widely varying costs. Cost-per-use and a comparison of interlibrary loan to subscription costs provided evidence of the effectiveness of collection development practices. However, at the individual journal title level, there was little overlap between the various indicators of journal value, with the highest ranked, or most valuable, journals differing depending on the indicator considered. Few of the articles studied appeared in open access journals, suggesting a possible focus area for the scholarly communications program. Conclusions – Knowledge of publication patterns provides an additional source of data to support collection development decisions and scholarly communications programming. As the estimated value of a journal is dependent on the factor being studied, gathering knowledge on a number of factors and from a variety of sources can lead to more informed decision-making. Efforts should be made to expand data considered in areas of scholarly communications and collection development beyond usage to incorporate publishing activities of institutionally affiliated authors.